Postoperative Circulating Tumor DNA as a Marker of Molecular Residual Disease in Stage II–III Colorectal Cancer: A Systematic Review - Alif Al-Mathari; Muhammad Yusuf; Arief Yanda (Lembaga Teewan Journal Solutions, 2026)
Postoperative recurrence remains a major challenge in stage II–III colorectal cancer (CRC) despite curative-intent surgery and adjuvant chemotherapy. Circulating tumor DNA (ctDNA) has emerged as a promising biomarker for detecting molecular residual disease (MRD) and for recurrence surveillance. This systematic review evaluated the prognostic utility of postoperative ctDNA in stage II–III CRC. Methods: A systematic review was conducted according to PRISMA guidelines, using PubMed/MEDLINE, Scopus, Web of Science, the Cochrane Library, and Google Scholar to identify studies published between 2015 and 2026. Eligible studies involved adults with stage II–III CRC undergoing curative-intent surgery and evaluated postoperative ctDNA in relation to recurrence or survival outcomes. Eight studies involving 1,557 patients were included. Postoperative ctDNA positivity was consistently associated with significantly increased recurrence risk and inferior oncologic outcomes, with reported hazard ratios ranging from 3.8 to 50.76. Serial ctDNA monitoring enabled recurrence detection approximately 5–10 months earlier than conventional imaging or carcinoembryonic antigen surveillance. Most studies demonstrated that ctDNA-guided management reduced the use of adjuvant chemotherapy without compromising recurrence-free survival. Postoperative ctDNA demonstrates strong prognostic value as a biomarker of MRD in stage II–III CRC and may facilitate more individualized postoperative surveillance and treatment strategies.